Water-logging and its’ impacts on livelihood: A study from Jashore Sadar Upazila, Jashore, Bangladesh (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Jashore, the south-western hub of Bangladesh has been facing elongated waterlogging and remains inundated for longer period of time over the year. The objectives of this study were to assess the main causes of water-logging and impacts on livelihood using historical rainfall and SRTM DEM (Digital Elevation Model) data and loss of agriculture using Landsat Multi Temporal data and validate it with people’s perception. A self-explorative semi structured questionnaire survey was performed with a total of 115 respondents were selected based on age (>50 years) and cultivable land (?30 decimals) from 5 Unions (Chanchra, Diara, Ichhali, Noapara, Ramnagar) and Jashore Sadar Municipality under Jashore District. Rainfall data were placid from Bangladesh Meteorological Department (BMD) and analysed through SPSS and figures were produced with Arc GIS software. The study revealed that the main causes of water logging were lack of adequate drainage path (58%) which was validated through GIS analysis, followed by excessive monsoon rainfall (42%), rapid growth of urbanization (16%), increased sediment/siltation (12%) and controlled river water flow due to guards construction (8%), respectively. The results showed that almost 90% area of Jashore Sadar Upazila had ?167mm rainfall and average monsoon rainfall were within 263 to 313mm. About 95.24% of male and 96.55% of female respondents’ told about the scarcity of fresh water during water-logging period and lost their homestead vegetable garden (94%), followed by unable to farming domestic birds (78%) and animals (64%), respectively. The result concluded that 84% of the respondents’ lost their agricultural crops and 52% respondents’ family members migrated to meet their livelihood during the water logging period. Dredging of Kobadak River should be the solution to allow regular tides of the river at first stage and helped to runoff the excessive rain water in the study area.
Keywords: Water scarcity; household chores; livelihood; bio-diversity; river dredging